2008
DOI: 10.1016/j.soncn.2007.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation and Lung Cancer: Oncology Nurses Can Make a Difference

Abstract: OBJECTIVES-Provide an overview of the impact of smoking after a diagnosis of lung cancer, discuss the relationship between smoking cessation and improved outcomes during the lung cancer trajectory, present information about tobacco dependence evidence-based treatments, reimbursement for these treatments, and tobacco-related resources available for patients and health care professionals, and emphasize the important role of nurses.DATA SOURCES-Published articles, reports, websites, and research studies.CONCLUSIO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 29 publications
(7 reference statements)
1
35
0
2
Order By: Relevance
“…The estimates for the prevalence of smoking at the time of lung cancer diagnosis have ranged from 24 to 60%, compared with 12–29% among the general US population [3,4,5,6,7]. Up to 83% of all smokers continue to smoke after a diagnosis of lung cancer [5,8,9]. Parsons et al [10] found in a review of 10 studies that people who continue to smoke after a diagnosis of early stage lung cancer almost double their risk of dying.…”
Section: Smoking Cessation: An Integral Part Of Lung Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimates for the prevalence of smoking at the time of lung cancer diagnosis have ranged from 24 to 60%, compared with 12–29% among the general US population [3,4,5,6,7]. Up to 83% of all smokers continue to smoke after a diagnosis of lung cancer [5,8,9]. Parsons et al [10] found in a review of 10 studies that people who continue to smoke after a diagnosis of early stage lung cancer almost double their risk of dying.…”
Section: Smoking Cessation: An Integral Part Of Lung Cancer Treatmentmentioning
confidence: 99%
“…Both chemotherapy and radiation treatment are likely to produce fewer complications and less morbidity among nonsmokers than smokers [5,45]. Smoking can have detrimental effects on the efficacy of chemotherapy including chemoresistance, chemoinsensitivity, and altered chemotherapeutic levels [5].…”
Section: Benefits Of Smoking Cessation For Lung Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Continued smoking following diagnosis is associated with decreased response to radiotherapy and chemotherapy, impaired wound healing, increased infections and circulatory problems, and late complications (eg, severe fibrosis, dysphagia). [5][6][7][8][9][10][11] Conversely, smoking cessation after diagnosis shows several medical benefits, such as decreased fatigue and shortness of breath, increased activity level and quality of life, and improved treatment toxicity. 12,13 The 2014 Surgeon General's report "The Health Consequences of Smoking-50 Years of Progress" (SGR) acknowledged causal relationships between smoking and adverse health outcomes among cancer patients, such as increases in overall mortality, cancer-specific mortality, and second primary cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Akciğer kanseri tanısı alan hastaların yaklaşık 2/3'ü sigara içmektedir (17,18) . Akciğer kanseri tanısı alanlarda kısa dönemde sigara bırakma oranları ise %37-79 arasında değişmektedir (19)(20)(21)(22) .…”
Section: Akciğer Kanseriunclassified